A case report of lung adenocarcinoma with polyserous effusions as the onset symptom. Issue 36 (September 2017) - Han, Ping; Yao, Ruipin; Zhai, Dongxia; Cheng, Chao; Yang, Fangyong; Sun, Shuai; Zhang, Danying; Yu, Chaoqin
Abstract: Rationale: Coexistence of lung adenocarcinoma and polyserous effusions is quite rare. This complexity of etiology adds difficulty to the diagnosis and is likely to cause misdiagnosis and maldiagnosis. Patient concerns: A 43-year-old woman was admitted with symptoms of dry cough, chest suffocation, polyserous effusions, and generalized edema. Only a small number of heterocysts were detected in the ascites, and malignant cells were detected in the pleural and pericardial effusions. After cytology tests of pericardial, pleural effusions, and ascites, puncture biopsy of the left lung lesion was performed with CT guidance, and immunohistochemical tests were performed. Diagnoses: The diagnosis of lung adenocarcinoma was histopathologically confirmed by puncture biopsy with CT guidance of the left lower lung lesion. Interventions: Combined treatments(pemetrexed/cisplatin) was administered after the left lung lesion immunohistochemistry. Outcomes: The patient has survived more than 1 year after pemetrexed/cisplatin combination chemotherapy. Lessons: Coexistence of lung adenocarcinoma and polyserous effusions is quite rare. Close attention should be paid whenever a patient with coexistence of ascites, pleural effusion, and pericardial effusion. More diverse methods could be helpful to identify the diagnosis and avoid misdiagnosis. Patients with advanced lung adenocarcinoma need individualized therapy, including pemetrexed/cisplatin combination chemotherapy.